The European Landing Obligation 2018
DOI: 10.1007/978-3-030-03308-8_14
|View full text |Cite
|
Sign up to set email alerts
|

Discard Avoidance by Improving Fishing Gear Selectivity: Helping the Fishing Industry Help Itself

Abstract: To address the challenges of the Landing Obligation, fishers need to be able to adjust the selective performance of each fishing operation in response to what they observe on the fishing grounds and to what they bring on board. This will include strategies on where and when to fish but also on how to fish, which we examine here. In particular, we focus on ways to encourage and support fishers to design, develop and test selective gears that will avoid unwanted catches in the first place. To this end, we highli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 58 publications
(60 reference statements)
0
16
0
Order By: Relevance
“…By using the data already available, we were able to predict the combined selectivity of multiple BRDs and quickly inspect a great number of potential BRD combinations, without the time and cost outlay associated with experimental investigation. The use of this approach could ultimately speed up the identification of promising gear designs, thus aiding the industry in pursuing individual catch goals (O'Neill et al, ). Moreover, the meta‐analytical approach allows to determine whether an increase in complexity in the gear design, that is no.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…By using the data already available, we were able to predict the combined selectivity of multiple BRDs and quickly inspect a great number of potential BRD combinations, without the time and cost outlay associated with experimental investigation. The use of this approach could ultimately speed up the identification of promising gear designs, thus aiding the industry in pursuing individual catch goals (O'Neill et al, ). Moreover, the meta‐analytical approach allows to determine whether an increase in complexity in the gear design, that is no.…”
Section: Discussionmentioning
confidence: 99%
“…Together with ecosystem‐based management approaches, BRDs have contributed to successfully reducing global discards of unwanted catches (Hall & Mainprize, ; Worm et al, ; Zeller, Cashion, Palomares, & Pauly, ). Nevertheless, continuous gear development is required for the industry to be able to cope with the variability in catch composition and management objectives (Kennelly & Broadhurst, ; O'Neill, Feekings, Fryer, Fauconnet, & Afonso, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…(2017) placed LEDs within a SMP and found that lights stimulated escape behaviour in haddock but not in cod. Also, when implementing light as a tool to manipulate fish behaviour, technical parameters such as colour, intensity, wavelength and strobing need to be considered (Ben-Yami, 1976; Marchesan et al ., 2005; O'Neill et al ., 2019), which can also vary depending on the fishing environment. For instance, fish vision is reduced in deep water due to the lower ambient light levels (Kim & Wardle, 1998).…”
Section: Introductionmentioning
confidence: 99%